2010
DOI: 10.1007/s00011-010-0203-7
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ agonist pioglitazone inhibits microglia inflammation by blocking p38 mitogen-activated protein kinase signaling pathways

Abstract: The results show that pioglitazone can inhibit LPS-stimulated microglia inflammation by blocking p38 MAPK signaling pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 20 publications
2
44
1
Order By: Relevance
“…Of interest is also that minocycline was ineffective in protecting neurons against this conditioned medium, but protected neurons against the toxicity of DEP in a co-culture system, indicating that the target for minocycline neuroprotection is microglia. Indeed, another reported inhibitor of microglia activation, the PPAR-γ agonist pioglitazone (Ji et al 2010; Drew et al 2015), also protected neurons from DEP-induced, microglia-mediated neurotoxicity.…”
Section: Discussionmentioning
confidence: 98%
“…Of interest is also that minocycline was ineffective in protecting neurons against this conditioned medium, but protected neurons against the toxicity of DEP in a co-culture system, indicating that the target for minocycline neuroprotection is microglia. Indeed, another reported inhibitor of microglia activation, the PPAR-γ agonist pioglitazone (Ji et al 2010; Drew et al 2015), also protected neurons from DEP-induced, microglia-mediated neurotoxicity.…”
Section: Discussionmentioning
confidence: 98%
“…Also, it has been reported that ERK or JNK inhibitors had no effect on PPARγ expression and loss by LPS stimulation. (41) Therefore, our results may show that sargaquinoic acid can inhibit the iNOS expression through the control of other signals, like NF-κB and JNK pathway, activated by LPS as well as PPARγ activation. Thus, we are currently investigating the effect of sargaquinoic acid on the PPARs activation, as well as the NF-κB DNA-binding activity and the PI3K/Akt signaling pathway in RAW264.7 macrophages.…”
Section: Discussionmentioning
confidence: 72%
“…iNOS and COX-2 were inhibited by rosiglitazone in rats (Cuzzocrea et al 2004). Studies also showed that pioglitazone inhibit lipopolysaccharide-induced inflammation block p38 phosphorylation (Ji et al 2010). So does rosiglitazone .…”
Section: Discussionmentioning
confidence: 94%